Study on Mechanism Construction and Path Innovation of Sports and Tourism Integration for Comprehensive Rural Revitalization in Guangdong, Hong Kong and Macao Greater Bay Area - He, Dongjin; Peng, Yijie; Han, Haolang; Wu, Gan; Zhou, Jiajun; Li, Yingmei (International Journal of Global Economics and Management, 2024)
With the rapid development of China's economy, the strategy of rural revitalization has become an important initiative to achieve balanced development of urban and rural areas. As an important economic region at the national strategic level, the rural revitalization of Guangdong, Hong Kong and Macao Greater Bay Area is particularly crucial. This paper explores the role of physical tourism integration in promoting rural revitalization in the Guangdong-Hong Kong-Macao Greater Bay Area, and analyzes the positive impacts of physical tourism integration on rural economy, society, culture and ecological environment. By constructing a theoretical framework and analyzing practical cases, this paper proposes a series of strategies and model innovations to promote the effective combination of body-tourism integration and rural revitalization. The findings suggest that physical tourism integration can significantly promote rural economic growth, foster social progress, strengthen cultural heritage, protect the ecological environment, and enhance rural brand image. The article concludes with policy recommendations and future research directions based on the findings of the study, aiming to provide theoretical and practical guidance for the realization of comprehensive rural revitalization.